Seismic interaction in linearly connected electrical substation equipment. - Der Kiureghian, A. (Earthquake engineering & structural dynamics.)
An electrical substation consists of a complex set of equipment items that are interconnected through conductor buses or cables. If the connections are not sufficiently flexible, significant dynamic interaction may occur between the connected equipment items during a seismic excitation. This interaction is believed to be responsible for some of the observed substation equipment damage in recent earthquakes. This paper investigates the interaction between two equipment items connected by a linear spring dashpot or spring dashpot mass element representing a conductor bus. It is found that the interaction between the two equipment items may significantly amplify the response of the higher frequency equipment item. The influences of various key parameters on the interaction effect are quantified. Means for reducing the adverse interaction effect are described.